TRANSFORMASI DIGITAL DESA SUKATANI PEMBUATAN PETA DIGITAL DIGITALISASI UMKM APLIKASI KAWAL DESA - Permana, Sulwan; Hariri, Rapi Muhamad; Nuralim, Taslim; Alfaruq, Muhammad Haikal; Rinjani, Nabila Putri; Nisa, Salma Aulia; Halimah, Silfi Nur; Rahayu, Puspa Arum; Faridah, Nayla Nur; Ramadhan, Muhamad Alfito Dwi; Hermawan, Tizar Azjah; harom, Ardi Nur; Prananta, Azfa; Fijannatika, Nazma Naya; Fadhil, Raja Naufal; Nazid, Sa’dan Frima M; Bayan, Alamahul; Sanusi, Muhamad Anwar; Rizal, Muhamad Saepul; Nursalim, Fathir Miftah; Nugraha, Yogi; Anwarushofa, Whina; Firdaus Irawan, Ferdy; Sulton, Restu (Institut Teknologi Garut, 2025)
Sukatani Village in Cisurupan District, Garut Regency has strong development potential, particularly in agriculture and micro, small, and medium enterprises (MSMEs). However, MSME marketing activities, village administration, and information dissemination have largely relied on manual methods. This program successfully increased digital literacy by 85% among 40 participating MSME actors, improved village administrative efficiency by 60% through the implementation of the Kawal Desa application, and produced a digital administrative map with 95% accuracy. Pre-test results showed that only 25% of MSME actors understood digital marketing, which rose to 90% in the post-test. Socialization of the Kawal Desa application was conducted for 15 village officials and 50 residents, resulting in enhanced transparency in village services. The creation of the village’s digital administrative map provides a clear representation of village boundaries, roads, rivers, the village office, and public facilities in Sukatani Village.